USAHA DIVERSIFIKASI USAHA PADA UMKM YUNSTO DONAT & SNACK DESA PURWOKERTO LOR KECAMATAN PURWOKERTO TIMUR KABUPATEN BANYUMAS (Universitas Wijayakusuma Purwokerto, 2023)
The purpose of the service is to provide an understanding of knowledge about product diversification and provide knowledge about business development. With product diversification / product diversification in its business, it makes its business continuity run well. Product diversification efforts can be in the form of: changes in variants, shapes, sizes, tastes, etc. This is because consumer demand varies, therefore there is a need for product diversification. Product diversification is a business or company strategy to meet the tastes and needs of the company and consumer needs through product diversification in the context of pursuit of growth, increase in sales, profitability and flexibility by creating new products or services without depending on a single type of product. Diverse products will make consumers believe that their various needs can be met fulfilled by the entrepreneur. The more variety of products offered to consumers, the greater the interest of consumers to buy products offered. The target of this community service is the owner of the Yunsto UMKM Business in Purwokerto Lor Village, East Purwokerto District, Banyumas Regency. The method used is the lecture method from the service team and providing additional capital assistance to help purchase raw materials, such as: wheat flour, cooking oil, refined sugar, ovalet, granulated sugar, etc. The results of the dedication were that the owner of the UMKM Yunsto in Purwokerto Lor Village became aware of the importance of product diversification and providing assistance to purchase donuts and snacks from the service team was received with pleasure by the owner of the Yunsto UMKM business.